2014
DOI: 10.15275/rusomj.2014.0104
|View full text |Cite
|
Sign up to set email alerts
|

Study of acute flaccid paralysis surveillance system in Kerman (Iran) for one decade

Abstract: Background -During the past decade, polio eradication has stalled globally. Acute flaccid paralysis (AFP) surveillance is a key strategy for monitoring the progress of polio eradication. All AFP patients who referred to expert committee were evaluated about the causes. Methods -This case series study is the result of activities for one decade of expert AFP committee of Kerman University of Medical Sciences from 2002-2011, with coverage of more than 2,650,000 populations and 730,677 child with age of ≤15 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…In this study, we found an increased incidence of AFP in 2009 and 2010, but no precipitating factor could be identified. Ebrahimi et al 21 in a similar study in Kerman, a region in central Iran, have also reported the increased incidence of AFP cases in 2009. Increasing incidence of AFP in this period may be caused by an infection, vaccination, and many other factors such as the increase in AFP incidence after vaccination.…”
Section: Discussionmentioning
confidence: 82%
“…In this study, we found an increased incidence of AFP in 2009 and 2010, but no precipitating factor could be identified. Ebrahimi et al 21 in a similar study in Kerman, a region in central Iran, have also reported the increased incidence of AFP cases in 2009. Increasing incidence of AFP in this period may be caused by an infection, vaccination, and many other factors such as the increase in AFP incidence after vaccination.…”
Section: Discussionmentioning
confidence: 82%